2018
DOI: 10.1002/ece3.3915
|View full text |Cite
|
Sign up to set email alerts
|

Nonadaptive female pursuit of extrapair copulations can evolve through hitchhiking

Abstract: Mounting evidence has indicated that engaging in extrapair copulations (EPCs) might be maladaptive or detrimental to females. It is unclear why such nonadaptive female behavior evolves. In this study, we test two hypotheses about the evolution of female EPC behavior using population genetic models. First, we find that both male preference for allocating extra effort to seek EPCs and female pursuit behavior without costs can be maintained and remain polymorphic in a population via frequency‐dependent selection.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Thus, whether this means that apparently nonadaptive extra‐pair mating behaviour by females can actually evolve remains unclear. Although recent theoretical work suggests that this might be true when the behaviour is selectively neutral or only slightly maladaptive (Lyu, Servedio, & Sun, ).…”
Section: Adaptive and Nonadaptive Hypotheses To Explain Variation Andmentioning
confidence: 99%
“…Thus, whether this means that apparently nonadaptive extra‐pair mating behaviour by females can actually evolve remains unclear. Although recent theoretical work suggests that this might be true when the behaviour is selectively neutral or only slightly maladaptive (Lyu, Servedio, & Sun, ).…”
Section: Adaptive and Nonadaptive Hypotheses To Explain Variation Andmentioning
confidence: 99%
“…Our results extend the current understanding of the direction of sexual selection and suggests the possibility that male preferences and female traits are more widespread in nature, only awaiting to be tested empirically. It has been suggested that in many animals cuckoldry may be an important source of selection pressure on behaviors or morphologies in both sexes 15 , 32 , thus the mechanism proposed by our models may be relevant in many species. We suggest that understanding the evolutionary consequences of the effect of cuckoldry deserves more attention.…”
Section: Discussionmentioning
confidence: 87%
“…The commonly accepted principle of cuckoldry is that the social father loses some paternity but can also potentially gain some extra paternity from engaging in additional mating with females that are already paired 48 . Whether cuckoldry is advantageous or disadvantageous to males thus depends on net yields 15 , 32 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation